Harmonizing Policy and Needs: Encouraging Autonomy of State Islamic Religious Universities for Responsive Student Admission Policies in the Regions - Witri Puji Astuti (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This policy paper presents a policy analysis of the challenges faced by State Islamic Religious Colleges (PTKIN) in the regions due to the centralized national student admissions policy. The main argument put forward is that this one-size-fits-all approach has created a significant gap between centrally-made policies and real needs at the local level, thus hampering PTKIN's strategic role as agents of regional development. This paper adopts William N. Dunn's policy analysis framework, which begins with the identification of relevant policy issues. The main issue, "Policy Mismatch with Local Needs," is analyzed through theoretical and conceptual approaches such as the Centralization-Decentralization Theory, the Policy Gap Theory, and the concept of Responsive Governance. This analysis is supported by a review of related regulatory documents, including Laws and Ministerial Regulations. Based on the root cause diagnosis, this article proposes five policy alternatives in the form of regulations, which are then evaluated using Dunn's alternative scoring to determine their feasibility and effectiveness. The analysis shows that revising the regulations to provide greater autonomy to PTKIN is the most effective solution. The proposed policy recommendation is for the Director General of Islamic Education to mandate regulatory changes that provide PTKIN with flexibility in setting selection criteria and admission quotas. In conclusion, harmonizing policies and needs through decentralization will ensure a fairer higher education system that is more responsive to local development dynamics.